Supply Chain Herding Behavior Management in Investment Decision among Investors at Indonesia Stock Exchange: Experimental Study on the Social Effect of Established Investors and the Informative Effect of Information Regarding Earning Per Share Value - Sri Rahayu; Abdul Rohman; Puji Harto; Mohamad Nur Utomo; Julia Safitri (International Journal of Supply Chain Management, 2020)
This research is aimed to conduct an empirital test on supply chain herding behavior of domestic investors in capital market in Indonesia by assuming that supply chain herding behavior is affected by the social effect of established investors and the informative effect of information regarding Earning Per Share (EPS) value. Motivation behind this research is a concern that many investors often make mistakes repeatedly in their investment decision, which later it forces them to suffer a great loss. This phenomenon is explained using Behavioral Finance Theory. The theory says that while making decision to invest, investors are affected more by irrational factor than rational factor. Research method was using 2x2 factorial experiment design that involved two factors and two indicators in each factor. The effect of two factors and also two indicators in each factor, either partially or simultaneously, on supply chain herding behavior in investment decision was tested. Data were collected by giving treatment to 100 investors. The collected data were processed for testing the hypothesis. Data analysis was done by determining mean difference value across the groups and examining the effect of independent variable on dependent variable.  Result of research shows that the social effect of the established investors who are skilled in investment analysis is more dominant and significant on investors’ decision to invest than the informative effect of information regarding EPS value. The implication of this result is that investors need to understand their psychological condition and strengthen their investment analysis skill. It is suggested that the next research should use biased psychology as variable or other indicator of accounting information that influences investment decision.